Balinese Social Investment in Death: Social Construction Perspective on Grave Conflict in Bali - I Nyoman Subanda; AAA Ngurah Sri Rahayu Gorda; I.G.A.AG Dewi Sucitawathi P (Universitas Pendidikan Ganesha, 2022)
This study aims to raise the phenomenon of traditional village conflicts based on conflicts over graves. Graves become meaningful for the Balinese people. Balinese people have to be buried in the traditional village of the community because it is recorded as the village manner where they are and wherever they migrate. This study uses a qualitative method that took place in Gianyar Regency. This research produces several significant results. First, the social investment model of the Balinese community in its existence as an indigenous community consists of two forms: the investment model for village institutions, in this case, the Pakraman or traditional village, and the investment model. Second, death has a profound meaning for the Balinese people, not only seen as the loss of one of the families in this world but also interpreted as the emergence of a new obligation in the form of an ancestral obligation that must be paid when someone dies. The person concerned is considered an ancestor, and when someone dies, he/she is considered an ancestor. Thus the obligation of the ancestors (Pitra Rna) shall be carried out by the relatives left behind. Third, in the context of Balinese society, graves are not only seen as a place to bury corpses but are also interpreted as a religious cosmic related to a series of ceremonies at one of the temples, which in the context of Balinese society is called Kayangan Tiga. This research finds new investment concepts and conflict-based social constructions that differ from the concepts of investment and social construction issued by Peter Berger.